Pattern of ocular trauma in Benghazi eye hospital, Benghazi, Libya - M Gebril (Libyan International Medical University Journal)
Background: This study was conducted to determine the pattern of ocular trauma in Benghazi- Libya. Methods: All cases of ocular trauma admitted to Benghazi eye hospital from January 2011 to August 2012 were retrospectively reviewed for open- or closed-globe injury (OGI or CGI). Data extracted included age, sex, residence, initial and final visual acuity (VA), cause and treatment of injury. The injuries were classified by Ocular Trauma Classification System. Results: Out of the 805 patients, there were 540 patients (67.0%) with Closed Globe Injury and 254 patients (31.5%) with Open Globe Injury and 11 patients (1.3%) with mixed trauma. Conclusion: This analysis shows a pattern of eye injury largely similar to reports from other parts of the world. Eye injury affected mainly younger age groups and road traffic accidents were the most common cause.